Uptake of the herbicide 2,4-dichlorophenoxyacetate (2,4-D) by Delftia acidovorans MC1 - complex kinetic characteristics in dependence of pH and growth substrate - Müller, Roland H.; Hoffmann, Doreen (Diffusion Fundamentals, 2005)
The uptake of the herbicide 2,4-dichlorophenoxyacetate (2,4-D) by the bacterial strain Delftia acidovorans MC1 was studied using 14C-labeled compound. Implication of active transport was suggested due to the effect of carbonylcyanide m-chlorophenylhydrazone (CCCP) as an uncoupler of the proton motive force, the presence of which reduced the uptake rate by up to 90%. Kinetic characteristics revealed a complex pattern that was strongly affected by the external pH. With 2,4-D-grown cells, the uptake characteristics followed a hyperbolic shape at pH 6.8 showing an intermediary plateau at ca. 20-100 μM 2,4-D. In contrast, the kinetics at pH 7.5 and 8.5 revealed a sigmoidal pattern. The maximum rate was obtained at around 400 μM 2,4-D, and amounted to 15-20 nmol/min*mg protein. Higher substrate concentrations led to inhibition. With cells grown on (RS)-2-(2,4-dichlorophenoxy)propionate [(RS)-2,4-DP], the uptake rate increased to about 65 nmol/min*mg protein which hints at substrate-dependent induction of specific carrier(s). With 2,4-D-grown cells, such a high rate was obtained only after cloning and expression of the tfdK gene, which encodes a specific transporter for 2,4-D. The uptake pattern of 2,4-D changed with mutant strains of MC1 that were phenotypically deficient of cleavage activity to ether bond in phenoxyalkanoate herbicides. Apparently, genes coding for proteins in uptake function were in addition deleted. With strains that lacked (R)-2,4-DP cleavage, the plateau disappeared and the kinetics followed a more continuous pattern. Strains that lacked (S)-2,4-DP cleavage showed faint 2,4-D uptake at all. The present picture hints at three proteins that are involved in 2,4-D uptake by active transport. With degradation-negative mutants of strain MC1, the influx of 2,4-D proceeded at a low rate. It was linearly dependent on the 2,4-D concentration correspond-ding to a micro-molar rate constant of 1.08*10-5 min-1 mg protein-1. The latter hints at 2,4-D influx into the cell by diffusion via cytoplasmic membrane at a low rate.